2016
DOI: 10.1177/1934578x1601101112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Sesame Seed Extract and its Constituents against β-Secretase

Abstract: The need for a preventive agent against dementia led us to screen natural plant resources. Among the herbs and spices tested, sesame seed prepared from Sesamum indicum seeds showed potent β-secretase inhibitory activity. The active principles were determined to be sesamin and sesamolin, typical lignans in S. indicum. The IC 50 values of sesamin and sesamolin were 257 and 140 μM, respectively. These compounds were investigated in a preliminary absorption experiment. After oral administration, these compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In a previous study, we reported that sesamin and sesamolin inhibited β‐secretase activity and were transported to the serum and brain in mice after oral administration (Matsumura et al, , c). However, the absorption rates of sesamin and sesamolin in mice are poor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous study, we reported that sesamin and sesamolin inhibited β‐secretase activity and were transported to the serum and brain in mice after oral administration (Matsumura et al, , c). However, the absorption rates of sesamin and sesamolin in mice are poor.…”
Section: Discussionmentioning
confidence: 96%
“…Sesame seeds and sesame oil have long been used as healthy foods in Asian countries including Japan, Korea, China, and India. We previously reported that sesamin and sesamolin inhibited β‐secretase activity (Matsumura et al, , c; Murata et al, ). Furthermore, we showed that sesamin and sesamolin were transported to the serum and brain in mice after oral administration (Matsumura et al, , c).…”
Section: Introductionmentioning
confidence: 94%
“…Using this strategy, we have already reported on its application to various crude extracts from plant resources to reveal their inhibitory activities and investigate their active constituents. [43][44][45] This method is expected to be recognized as an efficient strategy for natural product studies.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic, ginger, and cinnamon extracts were able to inhibit Aβ aggregation (Guo et al., 2010; Gupta et al., 2009; Peng et al., 2002). In another study, Sesamum indicum seeds and its active phytoconstituents sesamin and sesamolin showed BACE1 inhibitory activity (Matsumura et al., 2016).…”
Section: Introductionmentioning
confidence: 98%